Análisis de la Norma Técnica Peruana NTP-ISO 56005 - Gestión de la innovación - Herramientas y métodos para la gestión de la Propiedad Intelectual - Medina Plasencia, Ruddy (2025)
This article analyzes the Peruvian Technical Standard (NTP) ISO 56005:2021, which establishes guidelines for the management of intellectual property (IP) in the field of innovation. The standard provides tools and methods to identify, assess, protect and manage IP, allowing organizations to maximize the value of their intangible assets within a structured framework. Its importance in generating sustainable competitive advantages through the appropriate protection of inventions, brands and designs is examined, as well as its role in facilitating external collaborations, attracting investors and improving market positioning. The analysis addresses key aspects such as the creation of IP strategies aligned with business objectives, its integration into innovation processes, the promotion of an organizational culture that values IP, conducting audits, conflict management and regulatory compliance. Finally, success stories of foreign organizations that have implemented this standard with positive results are presented.